2015
DOI: 10.1186/s12967-015-0410-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-induced myeloid-derived suppressor cells promote tumor progression through oxidative metabolism in human colorectal cancer

Abstract: BackgroundExpansions of myeloid-derived suppressor cells (MDSCs) have been identified in human solid tumors, including colorectal cancer (CRC). However, the nature of these tumor-associated MDSCs and their interactions with tumor cells in CRC are still poorly understood.MethodsThe percentages and phenotype of MDSCs in peripheral blood and tumorous and paraneoplastic tissues from CRC patients, as well as the clinical relevance of these MDSCs, were assessed. Age-matched healthy donors were included as controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 44 publications
3
116
1
Order By: Relevance
“…Increases in circulating MDSCs correlate with disease progression in breast cancer patients 65 and circulating MDSCs in cancer patients are shown to inhibit T cell proliferation 64,65 . In our experiments, blood leukocytes from ranitidine-treated 4T1 tumor-bearing mice had less suppressive activity on antigen-driven T cell proliferation than those from control tumor bearing mice.…”
Section: Discussionmentioning
confidence: 49%
“…Increases in circulating MDSCs correlate with disease progression in breast cancer patients 65 and circulating MDSCs in cancer patients are shown to inhibit T cell proliferation 64,65 . In our experiments, blood leukocytes from ranitidine-treated 4T1 tumor-bearing mice had less suppressive activity on antigen-driven T cell proliferation than those from control tumor bearing mice.…”
Section: Discussionmentioning
confidence: 49%
“…This suggests that the reduction in arginase activity observed in these cells may have been related to the increase in the proportion of apoptotic and preapoptotic cells, although other mechanisms compromising their activity cannot, at present, be ruled out. Recruitment of tumor-promoting myeloid cells into colorectal carcinoma tumors (36) and liver metastases (49,50) has recently been reported by others. However, full characterization of these cells in hepatic metastases has been lacking.…”
Section: Mdscs In Hepatic Metastases Of Colorectal Carcinoma Patientsmentioning
confidence: 59%
“…S1A; refs. 15,17,18,24). Analysis of blood samples taken before the first ipilimumab treatment showed that the percentages of CD33 þ CD11b þ HLA-DR À MDSCs in the group of patients with melanoma was significantly higher (48.8 AE 2.3, P < 0.0001) as compared with HD (27.9 AE 1.7; Fig.…”
Section: Patientsmentioning
confidence: 89%